Virtual Clinical Internship Competencies of Medical Technology Students - Chua, Miguel Antonio; Justiniano, Bianca Felice; Ocampo, John Christian; Pamplona, Julienne Lizette; Pedarse, Liza Jane; Reyes, Yvonne; Martin, Gregorio; Navidad, Florence Co (International Journal of Arts, Sciences and Education, 2021)
Clinical internship is required during the fourth year of the Medical Technology (MT) degree program. This was adapted to a virtual setting amidst the COVID-19 pandemic. Due to the newly implemented strategy, it is important to determine whether the competencies required of the interns at the end of the program were attained. The research employed a descriptive, cross-sectional design conducted through online surveys with a sample of 98 fourth-year MT interns recruited through purposive homogeneous sampling. The survey contained 5-point Likert scales concerning their perception of their developed competencies, divided into 4 domains, based on learning outcomes, performance indicators, and objectives of the MT degree program and its internship. The Clinical Internship grade was also collected. Using IBM SPSS, the average was calculated for each domain per respondent as direct scores and the percentages, mean, standard deviation, and Spearman correlation coefficient were also computed. Results showed that the interns agree to the moderate extent that they attained the expected competencies after the virtual clinical internship and majority obtained a Clinical Internship grade higher than 2.00. Only Domain 2 (“the development of their well-rounded personality with a healthy outlook and oriented towards intelligent, ethical, and active participation in professional as well as community welfare activities”) was correlated with the grade of the respondents. These suggest that the virtual clinical internship was effective in the attainment of expected competencies of MT interns to a moderate extent, implying that the program implementation can still be improved to achieve a higher degree of attainment.